Inhaled and Systemic Steroids for Bronchopulmonary Dysplasia: Targeting Inflammation and Oxidative Stress - Francesca Galletta; Alessandra Li Pomi; Sara Manti; Eloisa Gitto (Antioxidants)
Bronchopulmonary dysplasia (BPD) remains a significant complication of preterm birth, characterized by impaired alveolar and vascular development, chronic lung inflammation, and long-term respiratory morbidity. Corticosteroids, both systemic and inhaled, have been widely investigated as potential therapeutic agents due to their anti-inflammatory properties and their emerging role in modulating oxidative stress. This narrative review explores the current evidence regarding the use of inhaled and systemic corticosteroids in the prevention and management of BPD, analyzing their efficacy, safety profiles, and long-term outcomes. While systemic corticosteroids, particularly dexamethasone, have demonstrated benefits in reducing ventilator dependence and lung inflammation, concerns regarding adverse neurodevelopmental effects have limited their routine use. Inhaled steroids have been proposed as a safer alternative, but their role in altering the disease trajectory remains controversial. A better understanding of the optimal timing, dosage, and patient selection is essential to maximize benefits while minimizing risks. Future research should focus on optimizing dosing strategies and identifying subgroups of preterm infants who may derive the greatest benefit from corticosteroid therapy.